Stripping of acetone from isopropanol solution with membrane and mesh gas-liquid contactors - Sun, Xiuyan; Constantinou, Achilleas; Gavriilidis, Asterios (My University, 2011)
Stripping of acetone from isopropanol utilizing nitrogen as a sweeping gas was conducted in gas/liquid contactors with slit type microchannels and containing flat sheet, metal and Teflon tortuous pore membranes or microfabricated metal meshes with straight pores. The contactor consisted of parallel metal plates, gaskets, and the membrane or the microstructured mesh so that passages for gas and liquid phases were formed. These slit type microchannels were 200 μm thick for both gas and liquid phases. All the membranes/meshes were wetted by the isopropanol solution. Breakthrough of one phase into the other was successfully described if contortion of the gas/liquid interface was considered at the pore ends. Various conditions during acetone stripping were investigated such as membrane type, gas and liquid flowrates and inlet acetone concentration. A contactor employing a Micro-Etch metal mesh with 76 μm openings and thickness of 50μm offered the lowest mass transfer resistance and resulted to the best acetone stripping performance. The separation efficiency increased by increasing the gas/liquid flowrate ratio, but was not affected when increasing the inlet acetone concentration. Good agreement between the experiments and an one-dimensional model with no adjustable parameters was observed.
Keywords: Separations; Mass transfer; Microchannel; Model